Synthesis, structure, and character of two rare earth carboxylic acid complexes. Issue 24 (17th December 2017) - Zhao, Ling-Yan; Ren, Li; Liu, Li-Wei; Wang, Li-Na
Abstract: Two rare earth carboxylic acid complexes, [Sm(MeBA)3 (2, 2′-bipy)]2 ·2(2, 2′-bipy) (MeBA = 3-methylbenzoic acid; 2, 2′-bipy = 2, 2′-bipyridine) (1 ) and [Pr(MeBA)3 (H2 O)2 ]n ∙n(4, 4′-bipy) (4, 4′-bipy = 4, 4′-bipyridine) (2 ), have been synthesized under hydrothermal conditions and structurally determined by single-crystal X-ray diffraction. Compound 1 is a dimer and further assembles into an infinite chain, two-dimensional net and three-dimensional supramolecular structure via weak π–π and C–H···π interactions. Some 2, 2′-bipy coordinates with Sm and some exist by non-covalent C–H···π interactions. Compound 2 is a 1D infinite chain structure, with adjacent 1D chains connected into a 2D layer structure by O–H···N hydrogen bonds. The two complexes were characterized by elemental analyses, IR, photoluminescence, and TGA. In order to illustrate subtle structural characteristics of intermolecular interactions and magnetic sensitivity of the complex, 2D-IR correlation spectra (2D-IR COS) under magnetic perturbation for 1 were performed. Abstract :